2020
DOI: 10.11613/bm.2020.020708
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement project: Reducing non-conformities of the samples for haemostasis testing in a secondary healthcare centre through the nurses’ education in phlebotomy

Abstract: Introduction: Poor compliance to the current guidelines and lack of knowledge among nurses about proper blood sampling is set as the study hypothesis. Here is presented a quality improvement project with following aims: a) to identify the most prevalent non-conformity of the samples for haemostasis testing, b) to identify the cause of sample non-conformity, c) to perform corrective action(s) and d) to assess the effectiveness of the corrective action(s). Materials and methods: The rate of non-conformity of sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…Simply knowing the error rate is insufficient for improving the quality of VBS; it is crucial to identify the sources and reasons behind these errors. Our findings support previous studies that have also demonstrated the association between inadequate training and lower quality of the blood sampling procedure ( 24 - 26 ). Continuous training is also recommended by the World Health Organisation (WHO) as a best practice for enhancing the quality of blood sample collection ( 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Simply knowing the error rate is insufficient for improving the quality of VBS; it is crucial to identify the sources and reasons behind these errors. Our findings support previous studies that have also demonstrated the association between inadequate training and lower quality of the blood sampling procedure ( 24 - 26 ). Continuous training is also recommended by the World Health Organisation (WHO) as a best practice for enhancing the quality of blood sample collection ( 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Research done in a tertiary care hospital in Turkey showed higher number of nurses (78%) who are unaware of proper identification procedure [4]. Two more studies performed in India and Croatia found 86.6% and 70% phlebotomists respectively who knew the proper identification process, which is much higher than our results [12,13].…”
Section: Discussioncontrasting
confidence: 78%
“…Another study done in Turkey showed a mere 6% of nurses which were aware of correct mixing protocol [11]. However, an analysis done in Europe found 47% subjects with correct response [13]. Probably missed especially in hours of heavy workload.…”
Section: Discussionmentioning
confidence: 99%
“…45 Some studies reported that the lack of knowledge of the practice (doctors or nurses) in several parts of the phlebotomy process was also the leading cause of error in the pre-analytical phase. 46,47 Another national study revealed that the knowledge on phlebotomy among Chinese nurses was unsatisfactory in some areas. 48 Thus, although innovative technology is required, standardized phlebotomy education programs were also highlighted.…”
Section: Discussionmentioning
confidence: 99%